Methodology for Ultrasonic Inspection of Dispersion Type U–Mo Fuel Plates - Navarrete-Villegas, A (Elsevier Ltd, 2020)
Nuclear fuel based on uranium-molybdenum alloys (U–Mo) showed a promising performance under irradiation tests, except for an undesirable interaction between the U–Mo fuel particles and the aluminum matrix. This development requires new methods and evaluation criteria for inspection of this fuel. Non-destructive analysis techniques, such as Ultrasonic Test (UT), can play a key role in the characterization and in-pile monitoring of test fuel plates, in particular, for the anisotropic fuel core. This paper proposes the establishment of a relationship between attenuation and transmission effects for U–Mo fuel plates with different uranium loads, based on mathematical processing of UT signals. For this purpose, the Chilean Nuclear Energy Commission (CCHEN) manufactured a set of 8 dispersion type test plates, with uranium loads from 1 to 8 gU/cm3. The U–Mo fuel plates were evaluated in transmission mode with a Panametrics PR 5800 pulser-receiver ultrasonic system, using frequencies of 20 and 25 MHz. The data set collected for each plate was processed using the Fourier Function transform of the data function in MATLAB®. The obtained results showed that the attenuation coefficient of the ultrasonic waves increased linearly as a function of the uranium load. From 12.3 dB/mm for 1 gU/cm3 to 74.2 dB/mm, for 8 gU/cm3. The transmission percentage of the signal reduces linearly as a function of uranium load and the grain boundaries present in the Al cladding, decreasing from 66.7% for 1 gU/cm3 to 9.1% for 8 gU/cm3. In conclusion, the uranium load and the metal forming processes strongly affects the response of the fuel plates subjected to UT scanning. These results established an acceptance criterion for fuel plates based on this response, and the transformations experienced by the fissile U–Mo material. © 2020 Elsevier Ltd